(untitled) (Nigerian Journal of Technology, 2002)
A solution is obtained for simply supported rectangular plates based on the Galerkin vector strain function approach of elasticity. Sinusoidal, uniform and partial loads are studied and detailed numerical results are presented for plates with different a/h ratios. And in the light of the present elasticity results, those obtained using Classical and Reissner theories and those given by Lee based on Donnel’s three dimensional thick plate theory, are examined.c